2010
DOI: 10.1590/s0037-86822010000400025
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do grau de incapacidade dos pacientes com diagnóstico de hanseníase em serviço de dermatologia do estado de São Paulo

Abstract: RESUMOIntrodução: Hanseníase é doença infecciosa crônica que pode levar a incapacidade física. Métodos: Avaliou-se 167 prontuários de pacientes com diagnóstico de hanseníase, no período de 2003 a 2007, para investigação do grau de incapacidade no momento do diagnóstico. Resultados: A maioria (60%) dos pacientes apresentava incapacidade física no momento do diagnóstico; 34% grau I e 26% grau II. Observou-se que há relação direta entre a duração da doença e o grau de incapacidade. Conclusões: O diagnóstico da ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
21

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 5 publications
2
20
1
21
Order By: Relevance
“…The predominance of multibacillary forms is due, among many factors, to delayed diagnosis, which affects maintenance of the epidemiological chain and can serve as a source of increased transmission 14,17 . The borderline clinical form was the most prevalent form of leprosy in this study, corroborating the results of Alves et al 18 . It is known that the closer to the lepromatous pole, the greater the likelihood of developing disabilities 19 .…”
Section: Discussionsupporting
confidence: 93%
“…The predominance of multibacillary forms is due, among many factors, to delayed diagnosis, which affects maintenance of the epidemiological chain and can serve as a source of increased transmission 14,17 . The borderline clinical form was the most prevalent form of leprosy in this study, corroborating the results of Alves et al 18 . It is known that the closer to the lepromatous pole, the greater the likelihood of developing disabilities 19 .…”
Section: Discussionsupporting
confidence: 93%
“…Sua detecção precoce e controle dependem diretamente da participação integrada dos sistemas municipal, estadual e federal de saúde, desde as unidades básicas de saúde aos centros especializados. É importante que sejam realizados planejamentos de ações pela equipe de saúde, direcionadas à orientação do autocuidado e à prevenção das limitações funcionais dos pacientes na realização das suas atividades cotidianas, promovendo a reabilitação (7,8,9) . Diante do exposto, buscou-se investigar as alterações neurofuncionais apresentadas pelos pacientes com hanseníase, buscando também identificar seu perfil socioeconômico e clínico.…”
Section: Introductionunclassified
“…These often occur because infected individuals ignore symptoms such as reduced sensitivity and muscle strength or, depending on their culture, resort to traditional popular medicine for treatment 19 . When not diagnosed and treated early, leprosy is a chronic disease that can lead to physical incapacity 20 .…”
Section: Resultsmentioning
confidence: 99%
“…However, Alves et al 20 , in a study characterizing leprosy using a physical examination, reported that 100 patients, from a total of 167 patients with a diagnosis of leprosy at a dermatology service in the State of São Paulo, Brazil, exhibited some degree of physical disability, with 43 individuals (30 men and 13 women) showing grade 2 disability, totaling 43%, excluding grade 0. Although leprosy affects both sexes and all ages, it is more common in men 10 .…”
Section: Conflict Of Interest Referencesmentioning
confidence: 99%